Agroecology in school contributions to food sovereignty: the case of the viracocha foundation - Pitta Paredes, Maria Jose; Acevedo Osorio, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Agroecology in school constitutes a comprehensive alternative to generate an agro-alimentary culture in community and school environments through the coordination of areas of production, transformation, and consumption, which endeavors to promote relevant education for the rural sector. This article shows the results of a study analyzing the relation between production and adherence to the minutes of participants from the Viracocha Foundation in San Agustín, Huila, Colombia. Semi-structured interviews were carried out with leaders and participants in two Foundation’s programs. The research findings determine that transformations are produced if students have contact with the farm, the kitchen, and the dining room. In this sense, the agricultural process articulates with human nutrition not only in school environments, but also within the community through programs promoted by the Foundation. It is concluded that agroecology in school is an appropriate educational strategy that can be incorporated into the education system and school feeding to facilitate the creation of healthy food production, preparation, and consumption spaces linking students to the configuration of an agro-alimentary culture based on a sustainable production and responsible consumption approach.